(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Background: benzodiazepines (BDZs) highly increase the risk of adverse drug reactions (ADRs), especially in the elderly with certain medical conditions. Methods: point-prevalence study in December 2017; 2,456 patients ≥65 years were included from 14 regional public and private hospitals, 24 long-term chronic care facilities (LTCCFs) and 20 nursing homes (NHs). Data regarded BDZ prescriptions and comorbidities, co-prescriptions, or concurrent diseases, which could increase the risk of ADRs in BDZ users. Univariate and multivariate logistic regression analyses were used to assess associations between ADRs in BDZ users vs. non-users, as well as within users. Results: 671 patients were prescribed BDZ, whose half were in NHs. Being prescribed 10 or more drugs was twice more common among BDZ users compared to non-users. BDZs were prescribed for long-term to 80% of patients in NHs, while proportions were halved in hospitals and LTCCFs. In the analyses within BDZ users, patients in NHs and LTCCFs were at higher risk of dementia and concurrent use of opioid analgesic and antipsychotics compared to hospitalized patients. Conclusions: the use of BDZs in older patients is common in FVG. A great extent of comorbidities and concurrent medications at higher risk of ADRs was found. Analyses in different healthcare settings can allow to drive evidence-based interventions in order to discourage the use of BDZs and monitor the raise of ADRs.